Aluminum chloride–catalyzed C-alkylation of pyrrole and indole with chalcone and bis-chalcone derivatives. Issue 4 (16th February 2016) - Gürdere, Meliha Burcu; Özbek, Oguz; Ceylan, Mustafa
ABSTRACT: The AlCl3 -catalyzed alkylation of pyrrole (2 ) with chalcone (1a–i ) at a ratio of 8:1 in the presence of 10 mol% AlCl3 gave the solely 2-alkyl pyrroles (3a–i ) at room temperature for 12 in good yields. The same reaction was performed with pyrrole (2 ) and chalcone at a ratio of 1:3 in CH3 CN at rt for 3 h to achieve 2, 5-dialkyl pyrroles (4a–f ). In addition, the reaction of the pyrrole (2 ) and indole (7 ) on 1, 4-phenylene bis-chalcones (5a–g ) at the ratio of 8:1 at rt for 24 h gave the double-addition products6a–g and8a–g in good yields, respectively. The structure of the products was confirmed by 1 H and 13 C NMR spectroscopy and elemental analysis. GRAPHICAL ABSTRACT: